Generating enhanced mucosal immunity against Bordetella pertussis: current challenges and new directions - Caulfield, Amanda D.; Callender, Maiya; Harvill, Eric T. (Frontiers in Immunology, 2023)
Bordetella pertussis (Bp) is the highly transmissible etiologic agent of pertussis, a severe respiratory disease that causes particularly high morbidity and mortality in infants and young children. Commonly known as “whooping cough,” pertussis is one of the least controlled vaccine-preventable diseases worldwide with several countries experiencing recent periods of resurgence despite broad immunization coverage. While current acellular vaccines prevent severe disease in most cases, the immunity they confer wanes rapidly and does not prevent sub clinical infection or transmission of the bacterium to new and vulnerable hosts. The recent resurgence has prompted new efforts to generate robust immunity to Bp in the upper respiratory mucosa, from which colonization and transmission originate. Problematically, these initiatives have been partially hindered by research limitations in both human and animal models as well as potent immunomodulation by Bp. Here, we consider our incomplete understanding of the complex host-pathogen dynamics occurring in the upper airway to propose new directions and methods that may address critical gaps in research. We also consider recent evidence that supports the development of novel vaccines specifically designed to generate robust mucosal immune responses capable of limiting upper respiratory colonization to finally halt the ongoing circulation of Bordetella pertussis.